Pengaruh Lifestyle, Brand Image, Kualitas Produk Dan Store Image Terhadap Keputusan Pembelian Pada Toko Three Second Malang - Rismalasari Rismalasari; Afi Racmat Slamet; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was purpose to determine the effect of lifestyle, brand image, product quality and store image on purchasing decisions at the Three Second store located at Jl. Soekarno Hatta No.A3, Kav.3, Jatimulyo, Lowokwaru, Malang City, East Java 65141. The method used is explanatory research which aims to explain the position of each variable and its effect between one variable with another variable, and the data source used primary method is by distributing likert scale questionnaires to respondents who have visited or bought Three Second products. The sample calculation in this study uses the Slovin formula which produces 87 respondents. The results of this research variable lifestyle, brand image, product quality and store image partially have a significant on purchasing decisions and simultane variables together have a significant effect on purchasing decisionsKeywords: Lifestyle, Brand Image, Quality Product, Store Image and Purchasing Decision.